Metal-Free One-Pot Protocol for the Preparation of Unexpected Carbazole Derivative in Water: Easy Access to Pyrimidocarbazole and Pyridocarbazolone Derivatives - Biswas, Soumen; Majee, Debashis; Dagar, Anuradha; Samanta, Sampak (Synlett, 2014)
A novel, one-pot, metal-free-based catalytic system for the synthesis of a series of functionalized 1-methoxycarbonyl-2-aryl/alkyl-9H-carbazole derivatives has been successfully achieved in water medium by the combination of methyl 2-(3-formyl-1H-indol-2-yl)acetate with aryl/alkyl-substituted β-acroleins using DABCO (20 mol%), followed by treatment of HCl under air at heating conditions. This sequential one-pot protocol provides moderate to good yields (51–68%) of aforesaid compounds. In addition, biologically important carbazole-fused new heterocyclic scaffolds can be synthesized through our procedure.
Keywords: one-pot sequential; organocatalyst; carbazole; water; pyrimidocarbazole; pyridocarbazolone